Lions and brown bears colonized North America in multiple synchronous waves of dispersal across the Bering Land Bridge - Alexander T. Salis; Sarah C. E. Bray; Michael S. Y. Lee; Holly Heiniger; Ross Barnett; James A. Burns; Vladimir Doronichev; Daryl Fedje; Liubov Golovanova; C. Richard Harington; Bryan Hockett; Pavel Kosintsev; et al. (Molecular Ecology, 2022)
The Bering Land Bridge connecting North America and Eurasia was periodically exposed and inundated by oscillating sea levels during the Pleistocene glacial cycles. This land connection allowed the intermittent dispersal of animals, including humans, between Western Beringia (far northeast Asia) and Eastern Beringia (northwest North America), changing the faunal community composition of both continents. The Pleistocene glacial cycles also had profound impacts on temperature, precipitation and vegetation, impacting faunal community structure and demography. While these palaeoenvironmental impacts have been studied in many large herbivores from Beringia (e.g., bison, mammoths, horses), the Pleistocene population dynamics of the diverse guild of carnivorans present in the region are less well understood, due to their lower abundances. In this study, we analyse mitochondrial genome data from ancient brown bears ( Ursus arctos ; n = 103) and lions ( Panthera spp.; n = 39), two megafaunal carnivorans that dispersed into North America during the Pleistocene. Our results reveal striking synchronicity in the population dynamics of Beringian lions and brown bears, with multiple waves of dispersal across the Bering Land Bridge coinciding with glacial periods of low sea levels, as well as synchronous local extinctions in Eastern Beringia during Marine Isotope Stage 3. The evolutionary histories of these two taxa underline the crucial biogeographical role of the Bering Land Bridge in the distribution, turnover and maintenance of megafaunal populations in North America.

Continental‐scale acoustic telemetry and network analysis reveal new insights into stock structure - Elodie J. I. Lédée; Michelle R. Heupel; Matthew D. Taylor; Robert G. Harcourt; Fabrice R. A. Jaine; Charlie Huveneers; Vinay Udyawer; Hamish A. Campbell; Russell C. Babcock; Xavier Hoenner; Adam Barnett; Matias Braccini; et al. (Fish and Fisheries, 2021)
Delineation of population structure (i.e. stocks) is crucial to successfully manage exploited species and to address conservation concerns for threatened species. Fish migration and associated movements are key mechanisms through which discrete populations mix and are thus important determinants of population structure. Detailed information on fish migration and movements is becoming more accessible through advances in telemetry and analysis methods however such information is not yet used systematically in stock structure assessment. Here, we described how detections of acoustically tagged fish across a continental‐scale array of underwater acoustic receivers were used to assess stock structure and connectivity in seven teleost and seven shark species and compared to findings from genetic and conventional tagging. Network analysis revealed previously unknown population connections in some species, and in others bolstered support for existing stock discrimination by identifying nodes and routes important for connectivity. Species with less variability in their movements required smaller sample sizes (45–50 individuals) to reveal useful stock structure information. Our study shows the power of continental‐scale acoustic telemetry networks to detect movements among fishery jurisdictions. We highlight methodological issues that need to be considered in the design of acoustic telemetry studies for investigating stock structure and the interpretation of the resulting data. The advent of broad‐scale acoustic telemetry networks across the globe provides new avenues to understand how movement informs population structure and can lead to improved management.

Divergent evolutionary processes associated with colonization of offshore islands - Natália Martínková; Ross Barnett; Thomas Cucchi; Rahel Struchen; Marine Pascal; Michel Pascal; Martin C. Fischer; Thomas Higham; Selina Brace; Simon Y. W. Ho; Jean‐Pierre Quéré; Paul O'Higgins; et al. (Molecular Ecology, 2013)
Oceanic islands have been a test ground for evolutionary theory, but here, we focus on the possibilities for evolutionary study created by offshore islands. These can be colonized through various means and by a wide range of species, including those with low dispersal capabilities. We use morphology, modern and ancient sequences of cytochrome b ( cytb ) and microsatellite genotypes to examine colonization history and evolutionary change associated with occupation of the O rkney archipelago by the common vole ( M icrotus arvalis ), a species found in continental E urope but not in B ritain. Among possible colonization scenarios, our results are most consistent with human introduction at least 5100 bp (confirmed by radiocarbon dating). We used approximate B ayesian computation of population history to infer the coast of Belgium as the possible source and estimated the evolutionary timescale using a Bayesian coalescent approach. We showed substantial morphological divergence of the island populations, including a size increase presumably driven by selection and reduced microsatellite variation likely reflecting founder events and genetic drift. More surprisingly, our results suggest that a recent and widespread cytb replacement event in the continental source area purged cytb variation there, whereas the ancestral diversity is largely retained in the colonized islands as a genetic ‘ark’. The replacement event in the continental M . arvalis was probably triggered by anthropogenic causes (land‐use change). Our studies illustrate that small offshore islands can act as field laboratories for studying various evolutionary processes over relatively short timescales, informing about the mainland source area as well as the island.

Phylogeography of lions ( Panthera leo ssp.) reveals three distinct taxa and a late Pleistocene reduction in genetic diversity - ROSS BARNETT; BETH SHAPIRO; IAN BARNES; SIMON Y. W. HO; JOACHIM BURGER; NOBUYUKI YAMAGUCHI; THOMAS F. G. HIGHAM; H. TODD WHEELER; WILFRIED ROSENDAHL; ANDREI V. SHER; MARINA SOTNIKOVA; TATIANA KUZNETSOVA; et al. (Molecular Ecology, 2009)
Lions were the most widespread carnivores in the late Pleistocene, ranging from southern Africa to the southern USA, but little is known about the evolutionary relationships among these Pleistocene populations or the dynamics that led to their extinction. Using ancient DNA techniques, we obtained mitochondrial sequences from 52 individuals sampled across the present and former range of lions. Phylogenetic analysis revealed three distinct clusters: (i) modern lions, Panthera leo ; (ii) extinct Pleistocene cave lions, which formed a homogeneous population extending from Europe across Beringia (Siberia, Alaska and western Canada); and (iii) extinct American lions, which formed a separate population south of the Pleistocene ice sheets. The American lion appears to have become genetically isolated around 340 000 years ago, despite the apparent lack of significant barriers to gene flow with Beringian populations through much of the late Pleistocene. We found potential evidence of a severe population bottleneck in the cave lion during the previous interstadial, sometime after 48 000 years, adding to evidence from bison, mammoths, horses and brown bears that megafaunal populations underwent major genetic alterations throughout the last interstadial, potentially presaging the processes involved in the subsequent end‐Pleistocene mass extinctions.